Pengaruh gadget, suasana belajar, iklim sekolah terhadap hasil belajar melalui minat belajar - Darmila Franika; Yon Rizal; Nurdin Nurdin (FKIP Unila, 2019)
The purpose of this research is to discover the effect of gadget as learning platform, the learning process, and the school environment that effect the second grade student’s achievement in Economic subject through their interest, especially the Social students in the second grade of MAN 1 Tanggamus in batch 2018/2019. The method used is the verification descriptive with ex post facto approach and survey. The participants of this research are the second grade of Social students of MAN 1 Tanggamus that consist of 93 students as the sample which the data obtained through probability sampling method and simple random sampling. The finding of this research described that there are several effects of using gadget as learning platform, the learning process and the school environment toward the result in the students’ outcome through the second grade of students’ interest of MAN 1 Tanggamus in batch 2018/2019. Moreover, it can be evidence using F arithmetic F table or 25.752 2.48 and the Significance in amount of 0.000 0.05.Tujuan penelitian ini adalah untuk mengetahui pengaruh media pendidikan (gadget), suasana belajar dan iklim sekolah terhadap hasil belajar ekonomi melalui minat siswa kelas XI IIS MAN 1 Tanggamus Tahun pelajaran 2018/2019. Metode yang digunakan adalah deskriptif verifikatif dengan pendekatan ex post facto dan survei. Populasi dalam penelitian ini berjumlah 121 orang dan sampel 93 siswa yang diperoleh menggunakan teknik probability sampling dengan menggunakan simple random sampling. Hasil penelitian menunjukkan bahwa ada pengaruh penggunaan media pendidikan (gadget), suasana belajar dan iklim sekolah terhadap hasil belajar siswa melalui minat belajar siswa kelas XI IIS MAN I Tanggamus tahun pelajaran 2018/2019. Hal ini dibuktikan dengan Fhitung Ftabel atau 25,752 2,48 dan nilai Signifikansi sebesar 0,000 0,05. Kata kunci: Penggunaan media pendidikan (gadget), Suasana belajar, iklim sekolah, hasil belajar, dan minat belajar.